Participatory Video on Menstrual Hygiene: A Skills-Based Health Education Approach for Adolescents in Nepal - Ghimire S; Devkota B (Dove Medical Press, 2020)
Sudha Ghimire,1 Bhimsen Devkota2 1Graduate School of Education, Department of Health Education, Tribhuvan University, Kirtipur, Nepal; 2Mahendra Ratna Campus, Department of Health Education, Tribhuvan University, Tahachal, NepalCorrespondence: Sudha GhimireGraduate School of Education, Department of Health Education, Kantipur 44618, NepalTel +977 9841458534Email sudha.ghimire42@gmail.comAbstract: School adolescents who are in the formative years of their lives are in stark need of appropriate and innovative skills-based health education and information. In this paper, we aim to explain how the participatory video (PV) approach was used in exploring the issues concerning adolescent reproductive health, particularly on menstrual hygiene among school adolescents in Chitwan district of Nepal. The students were engaged in the PV process for more than 6 months. They were given smart android phones with a 15-megapixel camera to shoot the video. The school adolescents regarded PV as an innovative and participatory medium for developing their critical thinking skills, collaborative skills, communication skills, and creative skills, which are required in the twenty-first century.Keywords: adolescents, participatory video, menstruation, school